2014
DOI: 10.1039/c4ta00299g
|View full text |Cite
|
Sign up to set email alerts
|

Highly hydrogen permselective ZIF-8 membranes supported on polydopamine functionalized macroporous stainless-steel-nets

Abstract: Inspired by the bio-adhesive ability of the marine mussel, highly hydrogen permselective ZIF-8 membranes were prepared on polydopamine functionalized stainless-steel-nets (SSNs). With polydopamine functionalization of SSNs under mild conditions, the nucleation and growth of well-intergrown ZIF-8 membranes were promoted through the formation of strong non-covalent and covalent bonds, which was helpful to enhance the membrane's separation selectivity while maintaining high permeance. For binary mixtures at 100 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 39 publications
3
84
0
Order By: Relevance
“…This compound is an attractive ultramicroporous material (pore limiting diameter $ 0.34 nm) [6] with exceptional thermal and chemical stability. ZIF-8 membranes have a huge potential for the extraction of H 2 from gas mixtures [7,8] and are also considered for alkene/alkane separations [9,10] either by molecular sieving mechanisms, selective adsorption or/and surface diffusion. Unfortunately the current membrane synthesis methods provide neither a sufficient reproducibility on commercial supports (tubular and multichannel), nor a competitive cost/ effectiveness ratio.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is an attractive ultramicroporous material (pore limiting diameter $ 0.34 nm) [6] with exceptional thermal and chemical stability. ZIF-8 membranes have a huge potential for the extraction of H 2 from gas mixtures [7,8] and are also considered for alkene/alkane separations [9,10] either by molecular sieving mechanisms, selective adsorption or/and surface diffusion. Unfortunately the current membrane synthesis methods provide neither a sufficient reproducibility on commercial supports (tubular and multichannel), nor a competitive cost/ effectiveness ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study indicated that pre-modication of the support surface with PDA can be employed 38 as a simple and powerful strategy to improve the nucleation of MOFs and zeolites on the alumina support surface through the formation of strong covalent bonds with the MOF or zeolite crystals. [38][39][40] In the present work, therefore, we tried to prepare a dense ZIF-100 membrane on the premodied support with PDA. As shown in Fig.…”
Section: Synthesis Of the Zif-100 Membranementioning
confidence: 99%
“…[35][36][37] Recently, PDA-based synthesis of ZIF-8 and zeolite LTA membranes has been developed to improve their gas separation performance and reproducibility. [38][39][40] It can be expected, therefore, that ZIF-100 membranes prepared on PDA-functionalized supports will show higher gas separation performances and reproducibility of membrane preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attributing to its adhesive ability through non-covalent adsorption and covalent reaction [42], PDA is very effective to attach precursor species onto supports for the facile synthesis of dense and selective ZIF-8 membrane [43,44] and zeolite LTA membrane [45]. In the present work, we extend and develop this concept for in-situ growth of dense zeolite FAU molecular sieve membranes on PDA-modified α-Al 2 O 3 tubes, as shown in Fig.…”
Section: Introductionmentioning
confidence: 84%